PENGARUH BEBAN KERJA, STRES KERJA DAN MOTIVASI KERJA TERHADAP TURNOVER INTENTION DI PT COLAMASS SUKSES MANDIRI - -, CINDY NOVIA TASHA (SCIENTIA JOURNAL, 2025)
This study explores the influence of workload, job stress and work motivation on turnover intention among employess at PT Colamass Sukses Mandiri. Triggered by rising turnover rates, the research aims to assess whether internal work factors significantly affect employees intention to resign. A quantitative approach with associative descriptive methods was employed, using questionnaires completed by 103 respondents and analyzed via multiple linier regression. Results show that workload, job stress and work motivation significantly impact turnover intention, with each factor showing p-values below 0,05 threshold. This suggest that high workload and job stress levels increase employees desire to leave, while the work motivation is weakened. These findings emphasize the importance for companies to effectively manage workload, job stress and foster employee work motivation as part of their retention strategies. The study contributes to a deeper understanding of how internal workplace dynamics directly influence turnover intention.